2008
DOI: 10.1186/1745-7580-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale analysis of human heavy chain V(D)J recombination patterns

Abstract: Background: The processes involved in the somatic assembly of antigen receptor genes are unique to the immune system and are driven largely by random events. Subtle biases, however, may exist and provide clues to the molecular mechanisms involved in their assembly and selection. Large-scale efforts to provide baseline data about the genetic characteristics of immunoglobulin (Ig) genes and the mechanisms involved in their assembly have recently become possible due to the rapid growth of genetic databases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 44 publications
7
39
0
Order By: Relevance
“…The mean CDRH3 length in healthy donor human memory B cells (29,(48)(49)(50)) is 14 to 16 aa, while a length of 24 aa is 2 standard deviations above the mean (51). Strikingly, the other known glycan-V3 bNAbs have CDRH3 lengths of 18 to 24 aa, and the glycan-V3 antibodies reported here have lengths of 19, 20, or 26 aa (Table 1).…”
Section: Discussionmentioning
confidence: 75%
“…The mean CDRH3 length in healthy donor human memory B cells (29,(48)(49)(50)) is 14 to 16 aa, while a length of 24 aa is 2 standard deviations above the mean (51). Strikingly, the other known glycan-V3 bNAbs have CDRH3 lengths of 18 to 24 aa, and the glycan-V3 antibodies reported here have lengths of 19, 20, or 26 aa (Table 1).…”
Section: Discussionmentioning
confidence: 75%
“…These 6 residues include Val106 and Asp107, which together make the most critical contacts within the sialic-acid pocket. The predicted nontemplated nucleotide additions are somewhat fewer than average at the V-D junction and somewhat greater than average at the D-J junction (13).…”
Section: Resultsmentioning
confidence: 81%
“…It has contributions from V H 1∼2, D H 1∼1, and J H 6 and from Vκ3∼21 and Jκ2 (Table S3). The 19-residue heavy-chain CDR3 is of roughly average length (13). Its sequence in the mature antibody is the same as in the UCA.…”
Section: Resultsmentioning
confidence: 99%
“…On comparing the prevalence of specific IGHV, D and J gene families in B-ALL and BL with that in previously published studies on PBLs, [15][16][17] no statistically significant difference was found. In addition, the frequencies of IGHD and IGHJ gene segments were not significantly different between complete and incomplete rearrangements.…”
Section: Features Of Igh and Igk Rearrangementsmentioning
confidence: 69%
“…22 In addition, the frequencies of specific gene families were similar to those reported for normal PBLs. [15][16][17][18][19] The prevalence of specific IGHD and IGHJ gene segments was significantly different from that reported for BCP-ALL. 8 The remarkable predominance of incomplete rearrangements involving IGHD genes from the more upstream part of the IGHD region and the most downstream IGHJ6 segment Ig-based MRD assay in B-NHL/B-ALL F Lovisa et al suggests that, in BCP-ALL, most IGHD-J rearrangements likely represent secondary recombinations, deleting pre-existing D-J joinings.…”
Section: Discussionmentioning
confidence: 91%